PENGARUH ORIENTASI PASAR TERHADAP KINERJA UMK (USAHA MIKRO KECIL) PENGOLAH KUSEN DAN PINTU DI KOTA BANJARBARU KALIMANTAN SELATAN - Nurhasanah Nurhasanah; Muhammad Helmi; Arfa Agustina Rezekiah (Jurnal Sylva Scienteae, 2020)
This study aims to determine the effect of market orientation toward business performance on Micro Small Enterprises (MSEs) frame and door crafters in Banjarbaru, South Kalimantan. Customers orientation have effect whereas the competitor orientation and interfuctional coordination has not effect to business performance on MSEs performance of frame and door crafters in the city of Banjarbaru, South Kalimantan. The benefit of this research is to provide input to improve the orientation of competitors and always coordinate between functions within the company's organization in order to increase the business performance. The data was examined using PLS-SEM analysis techniques, with Smart-PLS3 software according to validity and reality had been tested. We can conclude that customer orientation has a significant effect on the company performance. The Tvalue in this counting is (3,494) and the p value is (0,0001). The orientation of the competitor has apositive insignificant influence on company performance, it can be seen in the value of the T value calculation, the results are (0.064) and the value of p value (0.507). Inter-functional coordination has a positive non-significant effect on company performance, it can be seen in the T value (0.664) and p value (0.507).Keywords: market orientation, customer orientation, competitor orientation and interfunctional coordination and business performance